'Day Zero', Hydraulic Citizenship and the Defence of the Commons in Cape Town: A Case Study of the Politics of Water and its Infrastructures (2017-2018) - Robins, Steven (Journal of southern African studies, 2019)
This article examines how the continuing drought and water crisis in Cape Town in 2017 and 2018 created the conditions for the increasing visibility and public awareness of water and its infrastructures. Following Susan Leigh Star's famous observation that infrastructure is typically invisible until it breaks down, this article shows how the threat of the total collapse of the water and sanitation system during the drought contributed to rendering water and its infrastructures politically legible. It also contributed to making infrastructural disparities more visible. For instance, while anti-privatisation activists established the Water Crisis Coalition (WCC) to challenge increased water tariffs and 'defend the commons' (that is, by calling for wider public access to the city's dozens of springs), many middle-class residents in the historically white suburbs sought to go 'off the grid' by purchasing water tanks, boreholes and using their swimming pools as water reservoirs. At the same time, new 'water facts' surfaced, revealing that while residents in impoverished informal settlements used only 4.7 per cent of the city's water, middle class Capetonians in the suburbs used over 70 per cent. Yet, as a result of increased tariffs and social and moral pressure, the latter drew on a variety of water conservation methods and technologies to reduce their consumption dramatically. This article examines these expressions of 'hydraulic citizenship', forms of civic activism that drew on the production and circulation of 'water facts' and moral and political claims to water, which were often contested by differentially situated citizens, activists, journalists, scientists and City of Cape Town officials. This contributed to a contentious politics of water and its infrastructures.